New regulations regarding falsified medicines in Romania - Cadar, Emin; Erimia, Cristina-Luiza (Technium BioChemMed, 2023)
One of the most important aspects of a medicinal product is represented by its quality assurance, which makes it safe and reliable to use. Unfortunately, in recent years, the counterfeit medicine industry has been growing steadily, which has necessitated the introduction of new regulations and methods to control the quality of medicines. In the first part of the study, the counterfeit product has been described and the methods by which it can be brought to market, with the development of the online environment being one of the main reasons for the growth of this illegal industry. The study continues with some examples of counterfeit pharmaceuticals and how they can be recognized by health professionals, and then the impact of these drugs on society today is presented. Finally, some ways to combat this phenomenon were presented, with an emphasis on the introduction of the serialization of medicines, a very important directive implemented by the OSMR. Counterfeiting of medicines is a global problem, and there is a need for increased and effective international coordination and cooperation to ensure the effectiveness of anti-counterfeiting strategies, particularly in relation to the sale of such products on the Internet. To this end, the Commission and the Member States should cooperate closely and support the ongoing work of international forums on this issue, such as the Council of Europe, Europol, and the UN.